Ranitidine bismuth citrate based dual and triple therapies in Helicobacter pylori eradication - Ahmet AYDIN; Fulya GÜNŞAR; Mustafa YILMAZ; Zeki KARASU; Ömer ÖZÜTEMİZ and Tankut İLTER and Müge TUNÇYÜREK (Turkish Journal of Gastroenterology, 2019)
-